Slavery and the Birth of the Black Church in the United-States - (:unkn) unknown (My University, 2014)
From the moment the first Africans were brought to the Americas, religious life has become a way to transcend a humiliating and desperate life. Their lives were made of long days of forced work, inhuman living conditions, punishments and ill treatments of all sorts. Religious practice gave them a window onto another world. Over the years, it has slowly become a space of freedom and unique expression. The Black Church acted as a social movement on behalf of the African-american community. It has become a place of freedom which gradually has supported the foundations of their political expression and their demand of social justice. Understandably, as religion has always played a central role in North America, it is no wonder that it would play a central function in the liberation of slaves. Between the ideals of a divided nation and those of a marginalized community, the article analyzes the birth of the African-american church during slavery. Then, it examines the impact of African-american protestantism in the Caribbean through the life of George Leile, the first African-american missionary in Jamaica.
Keywords: African Research